Uterus didelphys with unilateral obstructed hemivagina with hematometrocolpos and hematosalpinx with ipsilateral renal agenesis - Gaurav Jindal; Satish Kachhawa; G L Meena; Gopal Dhakar (Wolters Kluwer Medknow Publications, 2009)
Uterus didelphys with blind hemivagina and ipsilateral renal agenesis (Herlyn Werner-Wunderlich Syndrome) is a rare congenital anomaly. It mostly presents with severe dysmenorrhea and a palpable mass due to unilateral hematocolpos. A patient with dysmenorrhea from a double uterus and an obstructed hemivagina is a diagnostic dilemma because the menses are regular. We report a case of a 14-year-old girl with this condition who was diagnosed as uterus didelphys with unilateral hematocolpos and hydrosalpinx with ipsilateral renal agenesis on the basis of sonography and confirmed by laparoscopic examination.